Landscape of sign language research based on smartphone apps: coherent literature analysis, motivations, open challenges, recommendations and future directions for app assessment - Dianes A/P David Emmanuel, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Landscape of sign language research based on smartphone apps: coherent literature analysis, motivations, open challenges, recommendations and future directions for app assessment by Dianes A/P David Emmanuel, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan